Performance Optimization of Solar Water Heating Systems Using Molten Salt Thermal Energy Storage Across Varying Tilt Angles - Natrayan Lakshmaiya; Gobikrishnan Udhayakumar; Prem Kumar Reddy M; Karthick M; Ramya Maranan; Prabhu Paramasivam; Asefash Getachew Girma (Global Challenges)
Abstract This study proposes a novel approach to enhance the performance of solar water heating systems by integrating molten salt thermal energy storage (MSTES) and evaluating its effectiveness under varying tilt angles (15°, 30°, 45°, and 60°). While prior research has extensively explored solar collectors and conventional storage media, there have been limited studies that experimentally assessed the combined effect of MSTES and tilt angle optimization on thermal performance. To address this gap, a parabolic trough collector system is employed using a eutectic mixture of sodium nitrate and potassium nitrate, known for its high thermal stability and energy retention. Key performance metrics, including collector efficiency, heat transfer coefficient, and storage efficiency, are analyzed under different tilt configurations. Results revealed that a 60° tilt angle offered the best performance, achieving a collector efficiency of 75%, a heat transfer coefficient exceeding 880 W m−2 K, and a storage efficiency of 61% during peak solar radiation. These findings highlight the effectiveness of MSTES in maximizing solar energy absorption and storage, thereby contributing to the development of high‐efficiency solar thermal systems that are adaptable to diverse climatic conditions and energy demands.